1995
DOI: 10.1002/eji.1830251215
|View full text |Cite
|
Sign up to set email alerts
|

In susceptible mice, Leishmania major induce very rapid interleukin‐4 production by CD4+ T cells which are NK1.1

Abstract: Susceptibility of BALB/c mice to infection with Leishmania major is associated with a T helper type 2 (Th2) response. Since interleukin-4 (IL-4) is critically required early for Th2 cell development, the kinetics of IL-4 mRNA expression was compared in susceptible and resistant mice during the first days of infection. In contrast to resistant mice, susceptible mice exhibited a peak of IL-4 mRNA in their spleens 90 min after i.v. injection of parasites and in lymph nodes 16 h after s.c. injection. IL-12 and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
148
1
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 62 publications
6
148
1
2
Order By: Relevance
“…This is in contrast to previously published observations made in the murine model using subcutaneous infection in the footpad, where a rapid and intense production of IL-4 was detected in the draining lymph nodes of BALB/c mice but not mice of resistant strains. 17,22,23 In addition, although cytokine producing cells were detected in the skin at 24 h by immunohistochemistry, a similar number of IL-4 producing cells was observed in both C57BL/6 and BALB/c mice. The discrepancy in the early IL-4 production may be related to the different model of infection used, since there is evidence that the route of infection may lead to different disease phenotypes and different cytokine profiles.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is in contrast to previously published observations made in the murine model using subcutaneous infection in the footpad, where a rapid and intense production of IL-4 was detected in the draining lymph nodes of BALB/c mice but not mice of resistant strains. 17,22,23 In addition, although cytokine producing cells were detected in the skin at 24 h by immunohistochemistry, a similar number of IL-4 producing cells was observed in both C57BL/6 and BALB/c mice. The discrepancy in the early IL-4 production may be related to the different model of infection used, since there is evidence that the route of infection may lead to different disease phenotypes and different cytokine profiles.…”
Section: Discussionmentioning
confidence: 85%
“…The data obtained in the footpad model 17 indicated that a strong increase in IL-4 production during the first 24 h after infection of the susceptible BALB/c mice was the cause of the inability of these mice to cure infection. Therefore, expression of IL-4 and IFN-g mRNA in the draining lymph nodes was measured at 8, 16 and 24 h postinfection.…”
Section: Expression Of Mrna For Selected Cytokines and Cytokine Recepmentioning
confidence: 99%
“…Several experimental results also strongly support a requisite role of IL-4 in mediating both Th2 cell differentiation and susceptibility to L. major in BALB/c mice (11,12). In this context, prior studies from this laboratory have shown that susceptible BALB/c mice, in contrast to mice from resistant strains, exhibited a burst of IL-4 mRNA expression in CD4 ϩ T cells from the draining lymph nodes (LN) within 1 day after infection with L. major (13). This early burst of IL-4 expression occurred in a restricted population of V␤4-V␣8 CD4 ϩ T cells after cognate recognition of a single epitope of the Leishmania homologue (LACK) 4 (14) of mammalian RACK1 (15).…”
Section: In Balb/c Mice Il-4 Production During the Initial Phase Of mentioning
confidence: 79%
“…The Relative Contribution of IL-4 Receptor Signaling and IL-10 to Susceptibility to Leishmania major 1 Nancy Noben-Trauth, 2 * Rosalia Lira, 3 A cquired resistance to Leishmania major is associated with the development of a Th1-dominated response, with IFN-␥ as the key effector cytokine able to activate macrophages to kill intracellular parasites. In contrast, susceptibility to L. major has been attributed to a Th2 response dominated by high levels of IL-4 and low amounts of IFN-␥, establishing this as the prototypic model to study polarized Th2 responses in vivo (1,2).…”
mentioning
confidence: 99%
“…In contrast, susceptibility to L. major has been attributed to a Th2 response dominated by high levels of IL-4 and low amounts of IFN-␥, establishing this as the prototypic model to study polarized Th2 responses in vivo (1,2). In BALB/c mice, L. major is able to stimulate a burst of IL-4 production in the draining lymph node (LN) 4 as early as 16 h following s.c. infection (3). Much of the early IL-4 is thought to derive from an oligoclonal population of CD4 ϩ T cells with the V␤4 V␣8 TCR that recognize the Leishmania Ag Leishmania homolog of receptors for activated C kinase (4,5).…”
mentioning
confidence: 99%